Kultúraalapú városfejlesztés, kreatív városok - Fábián, Attila (Közép-Európai Közlemények, 2010)
The cultural economy gets more and more importance in the course of the development of modern towns. The high importance of culture in the life of cities has already been well-known for a long time (J. Jacobs, R. Florida, D. Throsby and others), although it had a supplementary or indirect role earlier. At present, the earlier producing branches are often replaced by the cultural economy in employment, capital investment and income production in the developed towns. There are several examples in Europe confirming it, where towns and regions of outdated structure are reorganizing their structure with cultural development. The local and regional politics can have a direct and greater effect on all this than on choosing the premises of transnational companies. In the present study I examine the role of culture in town-development and the importance of creative towns.